Analisis Kausalitas Intention to Use Seabank: Perceived Usefulness, Perceived Risk, dan Trust - Aldrian; Umi Widyastuti; Terrylina Arvinta Monoarfa (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to provide an explanation of the influence of perceived usefulness, perceived risk, and trust on intention to use the Seabank digital banking application, with trust serving as a mediating variable. The research adopts an associative method with a quantitative approach. Data were collected through the distribution of questionnaires to individuals residing in the Greater Jakarta area (Jabodetabek), aged 17 and above, who are interested in using the Seabank application. The sampling technique used is Non-Probability Sampling with a Purposive Sampling approach. A total of 110 respondents were analyzed. Data processing was conducted using SmartPLS version 4.1.0.9. The analytical techniques employed include outer model testing, inner model testing, path analysis, t-tests, and mediation analysis using the bootstrapping method. The results of the study indicate that: (1) Perceived Usefulness has a significant positive direct effect on Intention to Use; (2) Perceived Risk has a significant negative direct effect on Intention to Use; (3) Trust has a significant positive direct effect on Intention to Use; (4) Perceived Usefulness has a significant positive direct effect on Trust; (5) Perceived Risk has a significant negative direct effect on Trust; (6) There is a significant indirect positive effect of Perceived Usefulness on Intention to Use through Trust; and (7) There is a significant indirect negative effect of Perceived Risk on Intention to Use through Trust